Civil disobedience and constituent power. Issue 4 (2nd November 2015) - Nobles, Richard; Schiff, David
Abstract: This paper uses the example of civil disobedience to explore Luhmann's description of the constitution as structural coupling between law and politics. Civil disobedience highlights the paradox of constituent and constituted power. The claims made for constituent power provide a basis for challenging the current configuration and expression of constituted power. This paradox is first avoided in the legal system through that system's inability to recognise a legal right to disobey law. In turn, a political system that has, under conditions of modernity, increasingly second coded power as legality, has an ever decreasing capacity to include communications that acknowledge a right to disobey law. Civil disobedience is only able to operate within the political system in the form of protest, and is accommodated through the exercise of discretionary powers. However, juridification of those powers has the capacity to threaten this accommodation.